Penggunaan Bahasa Indonesia di Mall Royal Plaza Surabaya - Fadilla Zafira; Putri Febri Anggraeni; Dini Artika Sukma; Marisca Trianita Zamba; Muhammad Azzam Zidane (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The use of good and correct Indonesian in public spaces is very important, because language is the main thing in communicating or interacting with society. Using good and correct Indonesian can increase communication efficiency and increase the sense of unity among Indonesian people. In public spaces, especially shopping centers, the application of good, precise and correct Indonesian can have a positive impact on the development and progress of the nation. In addition, using the right and accurate Indonesian can also give the impression of professionalism and ability to adapt to different social environments. Unfortunately, however, many people pay little attention to using Indonesian properly and correctly, such as using non-standard Indonesian excessive use of foreign languages, and language that is rude or impolite. Therefore, awareness and efforts from all parties, especially the younger generation, are needed to improve the use of the Indonesian language and strengthen a sense of love for the homeland by applying good and correct use of the Indonesian language in the public sphere.Â